China-Pakistan economic corridor (CPEC) issues/barrier and imperatives of Pakistan and China - Muhammad Arshad; Zhao Haidong (Journal of Global Business Insights, 2017)
China-Pakistan Economic Corridor (CPEC) is blessing for Pakistan and China. China and Pakistan have best political relations. CPEC is going to boost up the economic relations between both countries. China’s participation in the development of Gwadar Port took the international attention. Planning the development of Gwadar port becomes an important content of CPEC. This way Gwadar port has entered into a new development period. Due to their potential impact on the strategic pattern of the Indian Ocean and because of its strategic importance, there is international repercussion, also have other difficulties such as cost, security issues in Pakistan and Power crises and other issues. This paper attempts to explain the challenges, due to security issues, culture difference, energy and political crises in Pakistan, conflict in Baluchistan, and external pressure. Finally, this paper discusses some specific measures of barriers, solutions and suggestions. CPEC will be a game changer on the regional canvas and is expected to bring prosperity and improve quality of life in general to the region and in particular to Pakistan. There is a dire need to take on board all the regional and global players by addressing their concerns for early establishment of CPEC.